A large accumulation of avian eggs from the late cretaceous of patagonia (Argentina) reveals a novel nesting strategy in mesozoic birds. - Mariela S Fernández (Public Library of Science (PLoS), 2013)
We report the first evidence for a nesting colony of mesozoic birds on Gondwana: a fossil accumulation in Late Cretaceous rocks mapped and collected from within the campus of the National University of Comahue, Neuquén City, Patagonia (Argentina). Here, Cretaceous ornithothoracine birds, almost certainly Enanthiornithes, nested in an arid, shallow basinal environment among sand dunes close to an ephemeral water-course. We mapped and collected 65 complete, near-complete, and broken eggs across an area of more than 55 m(2). These eggs were laid either singly, or occasionally in pairs, onto a sandy substrate. All eggs were found apparently in, or close to, their original nest site; they all occur within the same bedding plane and may represent the product of a single nesting season or a short series of nesting attempts. Although there is no evidence for nesting structures, all but one of the Comahue eggs were half-buried upright in the sand with their pointed end downwards, a position that would have exposed the pole containing the air cell and precluded egg turning. This egg position is not seen in living birds, with the exception of the basal galliform megapodes who place their eggs within mounds of vegetation or burrows. This accumulation reveals a novel nesting behaviour in Mesozoic Aves that was perhaps shared with the non-avian and phylogenetically more basal troodontid theropods.